Preface - Nowak, Andrzej J. (Computer Assisted Methods in Engineering and Science, 2017)
This special issue of the Computer Assisted Methods in Engineering and Science comprises selected papers presented during the Numerical Heat Transfer 2012 International Conference (NHT2012) . The conference was organised as a Special Interest Conference of the European Community on Computational Methods in Applied Sciences (ECCOMAS) grouping European associations with interests in the development and applications of computational methods in science and technology. The NHT2012 Conference was held on September 4–6, 2012 in Wrocław, Poland. Papers published in this special issue (and the papers realised in one of the nearest accompanying special issue CAMES) have been selected to demonstrate an overview of the conference topics as well as, to document the significant advances in numerical heat transfer.